2009
DOI: 10.1128/mcb.00210-09
|View full text |Cite
|
Sign up to set email alerts
|

p38 Mitogen-Activated Protein Kinase- and HuR-Dependent Stabilization of p21Cip1 mRNA Mediates the G1/S Checkpoint

Abstract: Activation of p38 mitogen-activated protein kinase (MAPK) plays an important role in the G 2 /M cell cycle arrest induced by DNA damage, but little is known about the role of this signaling pathway in the G 1 /S transition. Upregulation of the cyclin-dependent kinase inhibitor p21Cip1 is thought to make a major contribution to the G 1 /S cell cycle arrest induced by ␥ radiation. We show here that inhibition of p38 MAPK impairs p21Cip1 accumulation and, as a result, the ability of cells to arrest in G 1 in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
212
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(230 citation statements)
references
References 52 publications
(63 reference statements)
11
212
2
Order By: Relevance
“…N, naïve; A, activated. mRNA stability (38,41). In addition, p38 has been shown to promote Xbp-1s mRNA stability and Xbp-1 protein nuclear translocation (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N, naïve; A, activated. mRNA stability (38,41). In addition, p38 has been shown to promote Xbp-1s mRNA stability and Xbp-1 protein nuclear translocation (44).…”
Section: Discussionmentioning
confidence: 99%
“…MAP kinase p38 activates mRNA binding protein HuR, and HuR promotes IL-4 mRNA stability (40,41). Therefore, we measured p38 phosphorylation upon TCR activation in IRE1␣ KO T cells to determine whether reduced IL-4 mRNA stability is due to reduced p38 activation.…”
Section: Volume 288 • Number 46 • November 15 2013mentioning
confidence: 99%
“…AliouatDenis et al (2005) reported a p53-independent role for Chk2 in p21 induction and senescence. Moreover, the p38MAPK checkpoint pathway that regulates G2/M has recently been shown to regulate p21 function at the G1/S checkpoint in a p53-independent pathway (Lafarga et al, 2009). Considering the cross-talk between ATR and ATM pathways, and that replication stress and single-strand breaks may also lead to ATM activation (Ewald et al, 2007), it appears likely that p21 activation via p53-dependent or -independent mechanisms may hinder apoptosis induced by Chk1 inhibitors.…”
Section: Dna Damage Induced Apoptosis and Role Of Chk1mentioning
confidence: 99%
“…In fact, it was recently demonstrated that HuR is a direct substrate of p38 MAPK and that p38-dependent phosphorylation of HuR enhances its mRNA stabilizing activity (36).…”
Section: Hur Is a Crucial Regulator Of Uvb-induced Cox-2 Expression-tmentioning
confidence: 99%